The Nazi Titanic : the incredible untold story of a doomed ship in World War II - Watson, Robert P. 1962- (Da Capo Press, a member of the Perseus Books Group, 2016)
Introduction: history's secrets -- Part I. Opening act: Germany's Titanic -- A bold idea -- The queen of the Atlantic -- An urgent message -- Part II. Starring role: Nazi propaganda film -- Rewriting history -- Hollywood on the Rhine -- Raising the Titanic -- The celebrated Selpin -- A new star -- Blockbuster -- Part III. Third role: evacuation ship -- The tide of war changes -- Evacuation -- Neuengamme -- A cruel race -- Swedish savior -- Part IV. Final role: floating concentration camp -- Exodus -- Floating concentration camps -- In the bunker -- Operation Rainbow -- Death from above -- Waves -- Part V, Curtain call -- Final act -- Aftermath